Upregulation of DUSP14 Affects Proliferation, Invasion and Metastasis, Potentially via Epithelial–Mesenchymal Transition and Is Associated with Poor Prognosis in Pancreatic Cancer - Wei, Yajun (Cancer Manag Res, 2020)
BACKGROUND: There is a growing number of evidence which report the relationship of the dual-specificity phosphatases 14 (DUSP14) with physiological and pathological mechanisms in the human body. However, it is still not known what if any role DUSP14 plays in pancreatic cancer. MATERIALS AND METHODS: The study evaluates the levels of DUSP14 in the pancreatic cancer tissues and cell lines using Western blotting and qRT-PCR to assess the levels of the DUSP14 and epithelial–mesenchymal transition (EMT) biomarkers. After the DUSP14 was blocked, the following assays were performed: colony formation, assessments of scratch wound and transwell to examine the effects of DUSP14 on the proliferation, migration and invasion of the pancreatic cancer. RESULTS: Results showed that there was a significant increase in the level of DUSP14 expression both in the pancreatic cancer tissues and cell lines. Experimental downregulation of DUSP14 induced the inhibition of the capacity of proliferation, migration and invasion of the pancreatic cancer cells. Western blotting analyses showed changes in the levels of expression of the EMT biomarkers, which helped to determine the function of DUSP14 in EMT. CONCLUSION: In conclusion, we suggest that DUSP14 is a novel molecular target that can be used for the treatment of pancreatic cancer.